Tropical intraseasonal oscillations in CFSv2 during Boreal summer and winter. (12th December 2016) - Krishnamurthy, V.
ABSTRACT: The simulation of the tropical intraseasonal oscillations (ISOs) by a coupled model in the Indo‐Pacific region is examined in this study. The retrospective forecasts by the Climate Forecast System version 2 (CFSv2) of National Centers of Environmental Prediction for the period 1982–2010 have been analysed and compared with observation. The leading Indian monsoon intraseasonal oscillation (MISO) during the boreal summer and the Madden‐Julian Oscillation (MJO) during the boreal winter are extracted from daily precipitation anomalies in forecasts and observations by using a data‐adaptive method. The model forecasts from May initial conditions simulates the observed spatial structure, magnitude and the northward and eastward propagation of MISO reasonably well. Similar performance is also evident in the simulation of the eastward propagating MJO in forecasts from November initial conditions. In the simulation of both the MISO and MJO by the model, the zonal wind at lower level shows appropriate observed relation with the precipitation and coupling with convection. The observed phase relations between precipitation and low‐level relative vorticity and between precipitation and upper‐level divergence in the zonal and meridional propagations are captured by the model. However, the variance of the ISOs differs from observation in certain regions, and the phase of the ISOs exhibits wide differences among the ensemble members of the forecast and with the observation. Comparison with the earlier model, CFS version 1, shows that the space‐time structure and evolution of MISO and MJO are better simulated by CFSv2.